Pembuatan Srinatha pada Tata Rias Pengantin Bali Agung - Usodoningtyas, Sri; Kusstianti, Nia (Universitas Negeri Surabaya, 2020)
Srinatha is a dumanggal (crescent-shaped) decoration on the forehead of Bali Agung's bride to make it look elegant, beautiful and attractive. The method of forming Srinatha generally uses the finger gauge. This method often causes problems, because the fingers have different sizes, and so do the forehead brides have different sizes. The purpose of this study is to describe the technique of making Srinatha with traditional and proportional methods and to find the suitability of Srinatha between traditional methods and proportional methods. This type of research is descriptive qualitative. Data collection techniques with observation to provide an assessment of the work. The results of this study note that the making of srinatha by traditional methods relies on fingers and ignores the shape of the bride's forehead, making it difficult to produce an exact and symmetrical Srinatha. The proportional method is adjusted to visualize the bride's face and pay attention to the shape of the forehead. In terms of flexibility, symmetry, compatibility and accuracy with the face shape the proportional method is better than traditional methods. This research contributes an alternative method of making Srinatha by considering the shape of the face.